FORMULASI DAN UJI AKTIVITAS ANTIOKSIDAN SHEET MASK BIOSELULOSA MENGANDUNG MINYAK ATSIRI BUNGA KENANGA (Cananga odorata) - Farhamzah, Farhamzah; Yuniarsih, Nia; Mursal, Iin Lidia Putama; Anggraeni, Fera (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
The use of antioxidants can be administered orally or topically. Antioxidants are known to be better if given topically in topical dosage forms such as sheet masks, so it is necessary to make masks from natural ingredients that have high antioxidant activity such as Cananga odorata because they contain benzyl benzoate which has anti-free radical properties. This study aims to prove the preparation of biocellulose essence sheet mask containing Cananga odorata has antioxidant activity with concentrations of F1, F2 and F3. Antioxidant testing using the DPPH method. Evaluation of biocellulose sheet mask preparations includes the mask sheet weight test and the mask sheet thickness test. Evaluation of essence preparations includes organoleptic, pH, viscosity, irritation, and hedonic tests. The positive phytochemical screening results contained alkaloids, flavonoids, tannins, and saponins. The results of testing the antioxidant activity of Cananga odorata obtained an IC50 value of 4.027 ppm. Evaluation of essence preparations obtained homogeneous, pH (5.01-6.43), viscosity (400-600 cPs), no irritation occurred in volunteers. Cananga odorata has antioxidant activity in the weak to moderate category, IC50 results for each formula F1 184.212 ppm, F2 150.175 ppm, and F3 72.448 ppm. Based on these results it can be concluded that Cananga odorata can be formulated as an essence with strong antioxidant potential with an IC50 value of 4.027 ppm.